A fast stop-flow two-dimensional liquid chromatography tandem mass spectrometry and its application in food-derived protein hydrolysates. (16th April 2023) - Li, Wu; Huang, Junhong; Zheng, Lin; Liu, Wanshun; Fan, Liqi; Sun, Baoguo; Su, Guowan; Xu, Jucai; Zhao, Mouming
Graphical abstract: Highlights: A fast stop-flow 2DLC-MS was established for peptide separation and identification. UPLC Protein BEH SEC and HSS T3 columns were found to be an appropriate pair for 2D separation. Large sample volume but small fraction volume was suggested for 2DLC separation. Stop-flow 2DLC-MS was proved of high potential in peptidomic analysis. Abstract: Food-derived bioactive peptides have many outstanding features like high safety, easy absorption, etc. However, explorations of the peptides are suffering from the limited knowledge of sample composition and low efficiency of separation techniques. In this work, a fast stop-flow two-dimensional liquid chromatography tandem mass spectrometry (2DLC-MS) was designed and constructed in-house. For chromatographic system optimization, the effects of column pairs and fraction transfer volumes on separation performance were studied. The pair of Protein BEH SEC and HSS T3 columns was found of high orthogonality. The peak capacity detected by the optimized 2DLC reached 1165 (for corn protein hydrolysates), indicating high resolving power. Moreover, the number of peptides identified from corn, soybean and casein protein hydrolysates reached as high as 8330, 8925 and 7215, respectively, demonstrating the high potential of the system. This would help reveal the peptide composition and facilitate the research on exploring bioactive peptides from food-derived protein hydrolysates.